A new green index as an overall quantitative green performance indicator of a facility - Mustapha, Mohamad Asrul (Italian Association of Chemical Engineering (AIDIC), 2015)
In assessing the greenness of a facility, a few green performance indicators and assessment tools such as the Building Research Establishment Environmental Assessment Method (BREEAM), the Leadership in Energy and Environmental Design (LEED), and Green Building Index have been developed. Although these tools can help promote green building designs and operations, they do not provide a quantitative measure of the overall impact of a facility on the environment. This is due to the fact that most of the current green rating assessment tools utilise the point-based rating system. Such system has several limitations. First, it can only provide a relative measure of the greenness of a system. Secondly, the points awarded may not be consistent as it can vary from one assessor to another. Finally, the available rating tools do not provide a single indicator of the greenness of a system as each green element of a system is evaluated separately rather than as a whole. This paper presents a new tool for assessing the greenness of a facility that overcomes the aforementioned limitations. The use of the stock market composite index as a tool to assess the stock market performance has been extended to the domain of facility management that includes industrial and commercial buildings. The composite index has been utilised as the basis to develop a Green Index to assess and manage an organisation's level of greenness. The advantage of the composite index that could capture the movement of price within each stock and reflect it into a single composite index could be used in measuring and monitoring the impacts contributed by the individual green elements, on the environment. Results show that the formulation of the Green Index with weighting assignment using factor analysis would help organisations simultaneously optimise and improve their energy and water consumption, as well as waste generation. In addition, the Green Index graph provides facility managers with a graphical tool to visualise and gain insights on the performance trend of a facility.